Reliability and validity of maximal mean and critical speed and metabolic power in Australian youth soccer players - Lord, C.; Blazevich, A. J.; Abbiss, C. R.; Ma`ayah, F. (Journal of Human Kinetics, 2020)
The reliability and validity of maximal mean speed (MMS), maximal mean metabolic power (MMPmet), critical speed (CS) and critical metabolic power (CPmet) were examined throughout the 2016-2017 soccer National Youth League competitions. Global positioning system (GPS) data were collected from 20 sub-elite soccer players during a battery of maximal running tests and four home matches. A symmetric moving average algorithm was applied to the instantaneous velocity data using specific time windows (1, 5, 10, 60, 300 and 600 s) and peak values were identified. Additionally, CS and CP¬met values calculated from match data were compared to CS and CPmet values determined from previously validated field tests to assess the validity of match values. Intra-class correlation (one-way random absolute agreement) scores ranged from 0.577 to 0.902 for speed, and from 0.701 to 0.863 for metabolic power values. Coefficients of variation (CV) ranged from good to moderate for speed (4-6%) and metabolic power (4-8%). Only CS and CPmet values were significantly correlated (r = 0.842; 0.700) and not statistically different (p = 0.066; 0.271) to values obtained in a shuttle-running critical test. While the present findings identified match-derived MMS, MMPmet, CS and CPmet to be reliable, only CS and CPmet derived from match play were validated to a CS field test that required changes in speed and direction rather than continuous running. This suggests that both maximal mean and critical speed and metabolic power analyses could be alternatives to absolute distance and speed in the assessment of match running performance during competitive matches.